Atomic Decomposition of Weighted Lorentz Spaces and Operators - Eddy Kwessi; Geraldo de Souza; Fidele Ngwane; Asheber Abebe (Journal of Function Spaces)
We obtain an atomic decomposition of weighted Lorentz spaces for a class of weights satisfying the Δ2 condition. Consequently, we study operators such as the multiplication and composition operators and also provide Hölder’s-type and duality-Riesz type inequalities on these weighted Lorentz spaces.